Methods for prevention of acute post-endoscopic retrograde cholangiopancreatography pancreatitis - Kamil Jaszczuk; Michał Lipiński; Grażyna Rydzewska (Gastroenterology Review)
Acute pancreatitis is the most common complication of endoscopic retrograde cholangiopancreatography (ERCP), with incidence rates ranging between 2% and 16%. In addition to being experienced in endoscopic procedures and having knowledge of the patient qualification criteria, physicians should also be aware of the patient and procedure-related risk factors responsible for post-ERCP pancreatitis (PEP). Intrarectal administration of nonsteroidal anti-inflammatory drugs and pancreatic duct stenting were demonstrated to be efficient in high-risk patients. This review provides a broader summary of pharmacological methods and techniques aimed at reducing the risk of PEP.